Effects of drip irrigation levels on soil water, salinity and wheat growth in North China - Wang, Zhenhua; Liao, Renkuan; Lin, Henry; Jiang, Guojun; He, Xinlin; Wu, Wenyong; zhang, Lilizhong (International Journal of Agricultural and Biological Engineering, 2018)
Northwest China has long suffered from serious water scarcity and soil salinization. It is important to reduce the impact of soil salinization on crop growth and improve water-use efficiency (WUE) through efficient utilization of the limited water resources. This study examined the effects of drip irrigation (DI) on the water and salinity distribution in soil planted with spring wheat, a representative crop in Northwest of China. An in-depth analysis of the leaching of salts by irrigation water and salt accumulation in the soil profile was performed. An irrigation experiment with four irrigation levels (315 mm, 360 mm, 405 mm, and 450 mm) was conducted to investigate the effects of the amount of irrigation water (AIW) on the physiology and growth, photosynthesis, yield, and WUE of spring wheat. The results showed that applying the irrigation water at 405 mm can improve the distribution uniformity of soil water and WUE. Due to the leaching of salts by irrigation water, an increase in the AIW resulted in a higher desalination rate, a lower salt accumulation rate, and a greater depth of desalination. When the AIW was 315 mm, 360 mm, 405 mm and 450 mm, the average depth of desalination was 40 cm, 43 cm, 47 cm and 50 cm, respectively. The plant height, aboveground biomass, leaf area, and wheat ear mass varied significantly with the AIW. As the AIW increased, the average plant height increased, while the aboveground biomass, leaf area, and wheat ear mass increased first and then decreased. The net photosynthetic rate, transpiration rate, and stomatal conductance all increased greatly with increasing AIW, but excessive AIW could lower the net photosynthetic rate. The 405 mm treatment was the recommended irrigation level with the best wheat yield and water productivity at 7631.19 kg/hm2 and 1.88 kg/m3, respectively.Keywords: drip irrigation; spring wheat; spatial distribution; desalination; water use efficiencyDOI: 10.25165/j.ijabe.20181101.3775Citation: Wang Z H, Liao R K, Lin H, Jiang G J, He X L, Wu W Y, et al. Effects of drip irrigation levels on soil water, salinity and wheat growth in North China. Int J Agric & Biol Eng, 2018; 11(1): 146–156.